Genomic Positional Dissection of RNA Editomes in Tumor and Normal Samples - Chigaev, Michael; Yu, Hui; Samuels, David C.; Sheng, Quanhu; Oyebamiji, Olufunmilola; Ness, Scott; Yue, Wei; Zhao, Ying-yong; Guo, Yan (Frontiers in Genetics, 2019)
RNA editing is a phenomenon that occurs in both protein coding and non-coding RNAs. Increasing evidence shows that adenosine-to-inosine RNA editing can potentially render substantial functional effects throughout the genome. Using RNA editing datasets from two large consortiums: The Cancer Genome Atlas (TCGA) and the Genotype-Tissue Expression (GTEx) project, we quantitatively analyzed human genome-wide RNA editing events derived from tumor or normal tissues. We found that most common RNA editing sites tend to have a higher level of editing in tumors as compared to normal samples. Of the 14 tumor-normal-paired cancer types examined, 11 of the 14 cancers tested had elevated RNA editing levels in tumors. The editomes in cancer or normal tissues were dissected by genomic locations, and significant RNA editing locational differences were found between cancerous and healthy specimens. Our results indicated a significant correlation between the RNA editing rate and the gene density across chromosomes. Visualization of running RNA editing rates along chromosomes highlighted clusters of hyper RNA editing regions. We identified hyper RNA edited genes (protein-coding genes, lincRNAs, and pseudogenes) that embodied a large portion of cancer prognostic predictors. This study reinforces the potential functional effects of RNA editing in protein-coding genes, and also makes a strong foundation for further exploration of the role of RNA editing in non-coding regions.